Narratives on the 212 Movement and Tauhid Flag Transformation from the Boudieusian Perspective - Irfan Latifulloh Sarhindi; Rysa Sahrial (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2021)
The so-called Tauhid flag was exclusively known as HTI's (Hizbut Tahrir Indonesia) symbol of Islamic caliphate re-establishment. However, after its burning incident in 2018, the flag appears to be one of the symbols of post-Islamist populism. By using the Bourdieusian perspective's framework, this study aims to understand the prior narrative of the Tauhid flag, the narrative of the 212 movements, and how the narrative of the 212 movements influenced the transformation of the narrative of the Tauhid flag. The data in this study were taken from 180 sampled tweets using proportionate stratified random sampling. The data were elaborated with related news and publications and then condensed, codified, and categorized. This study revealed that the prior narrative of the Tauhid flag was the narrative of institutional Islamism, aiming to re-establish the Islamic caliphate through a peaceful act. Meanwhile, the 212 movements represent the narrative of post-Islamist populism. When the Tauhid flag became the central issue in several 212 movements, the flag's narrative transformed into post-Islamist populism. It means that the widespread acceptance of the Tauhid flag has a little impact, if none, on HTI's caliphate campaign.